Towards a Social and Human Factor Classification Related to Productivity in Software Development Teams (2020)
Software product development is characterized as an activity that focuses on social and human factors. In fact, studying these factors may be particularly appealing to software organizations seeking initiatives for fostering team productivity. In this light, the classification of the factors that may have an impact on the productivity of the software development team becomes the point of departure for the selection and definition of improvement strategies. As part of this research, we designed a methodology grounded in systematic literature review processes to approach a classification for social and human factors and develop a validation plan. In addition, the definition of inclusion and exclusion criteria yielded an approximation to the proposed classification, which may be used as the input for the definition of improvement actions. Finally, this work reports on the preliminary advances of the validation plan. © 2020, Springer Nature Switzerland AG.